Expert VB 2005 Business Objects, Second Edition - Lhotka, Rockford (Apress, 2012)
This book is about application architecture, design, and development in .NET using objectoriented concepts. The focus is on business-focused objects called business objects, and how to implement them to work in various distributed environments, including web and client/server configurations. The book makes use of a great many .NET technologies, object-oriented design and programming concepts, and distributed architectures. The first half of the book walks through the process of creating a framework to support object-oriented application development in .NET. This will include a lot of architectural concepts and ideas. It will also involve some in-depth use of advanced .NET techniques to create the framework. The second half of the book makes use of the framework to build a sample application with several different interfaces. If you wish, it’s perfectly possible to skip the first half of the book and simply make use of the framework to build object-oriented applications. One of my primary goals in creating the CSLA .NET framework was to simplify .NET development. Developers using the framework in this book don’t need to worry about the details of underlying technologies such as remoting, serialization, or reflection. All of these are embedded in the framework so that a developer using it can focus almost entirely on business logic and application design, rather than getting caught up in “plumbing” issues.